Legal Regulation of Certain Types of Transportation in the Republic of Kazakhstan: National and International Aspects - ALIPULY, Yerik (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The present article considers the legal and organizational problems of controlling the transport branch, in particular, the motor transport, in the Republic of Kazakhstan. The problems of transport receive much attention now. The government authorities, mass media, and preeminent members of the legal science actively discuss and look for the ways to solve transport problems; however, at the moment there are still many of them. Therefore, the studies connected to the creation of the perfect organizational and legal model of transport control are rather urgent. The purpose of this article is to analyze the organizational and legal base of transport control and, in particular, of controlling the sphere of motor transportation to determine the ways of improving the transport legislation. The article represents the list of the main problems connected to the use of the motor transport typical for the Republic of Kazakhstan and for other countries as well. It was shown that together with the civil regulation of the transport activity in the sphere of the motor passenger and cargo transportation, it is necessary to actively use the administrative and legal means of control, in particular, licensing, administration control and supervision, and administrative responsibility. The complex character of the legislation regulating the legal relations in the sphere of transport is emphasized. The main sources of the special legislation in the sphere of motor transportation are studied. The positive experience of the developed countries in the creation of the system of urban transport control and use of a transport infrastructure is analyzed; various models of control are shown. Following the results of consideration of the peculiarities of the transport control, the article formulates some offers aimed at improving the legislation of transport and transport infrastructure.